2021
DOI: 10.1186/s40529-020-00307-0
|View full text |Cite
|
Sign up to set email alerts
|

First records of powdery mildew fungi (Erysiphales) on medicinal plants in Taiwan

Abstract: Background Production of medicinal plants in Taiwan is not only hampered by international market competition, but also lack of knowledge of their pathogens, such as powdery mildew fungi (Erysiphales, Ascomycota). Records of these fungi in Taiwan originate from few researchers for the last one hundred years and are still incomplete. Since powdery mildews in tropical/subtropical environments rarely develop the sexual stages with morphologically diagnostic characteristics, internal transcribed spa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the present study, the occurrence periods of the PMs in the winter and spring imply they prefer mild weather instead of excessively high temperature (up to 35 • C) in summer, and it is suggested that the PMs in the subtropical regions may stay in a quiescent state in their hosts during hot summers. However, chasmothecia are rarely formed in subtropical and tropical environments [23,47,77,94]. Thus, the reservoirs of the PMs on all their possible hosts as mycelia or other structures are crucial for their survival and for the infection in the next season.…”
Section: Perennation Of Powdery Mildews In the Subtropics And The Imp...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the occurrence periods of the PMs in the winter and spring imply they prefer mild weather instead of excessively high temperature (up to 35 • C) in summer, and it is suggested that the PMs in the subtropical regions may stay in a quiescent state in their hosts during hot summers. However, chasmothecia are rarely formed in subtropical and tropical environments [23,47,77,94]. Thus, the reservoirs of the PMs on all their possible hosts as mycelia or other structures are crucial for their survival and for the infection in the next season.…”
Section: Perennation Of Powdery Mildews In the Subtropics And The Imp...mentioning
confidence: 99%
“…Subsequent studies related to this group of PMs in Taiwan can be referred in Kuo [15], Braun and Cook [2], and the List of Plant Diseases in Taiwan [16]. Additional investigations in recent years are those in Kirschner and Liu [17], Kirschner [18], Wang et al [19][20][21], Kirschner et al [22], Yeh et al [23], and Xiao et al [24].…”
Section: Introductionmentioning
confidence: 99%
“…The smallest AMPs were derived from jatropha curcas with seven amino acids [ 192 ]. Commonly found AMPs in plants are the cyclotide family, thionins, the α-Hairpinin family, Hevein-like peptides, lipid transfer protein, knottin-type peptides, snakins, and plant defensins [ 193 ]. Thionin is a useful AMP for the development of a glucose detection biosensor.…”
Section: Applications In Biomedical Sectormentioning
confidence: 99%